The first complete specimen of the deep-water shrimp Batella praecipua De Grave, 2004 (Crustacea: Decapoda: Alpheidae) - Ashrafi, Hossein; Ďuriš, Zdeněk; Anker, Arthur (Zootaxa, 2022)
The deep-water alpheid shrimp Batella praecipua De Grave, 2004 was originally described based on two incomplete specimens, both with their first chelipeds missing, collected at 400–440 m off New Caledonia. During the recent KANADEEP 1 expedition in the Coral Sea in 2017, the first complete specimen of B. praecipua was collected at a depth of 370–380 m. The morphology of this specimen is presented in detail, with emphasis on the highly diagnostic chelipeds, which are described and illustrated for the first time. A slight intraspecific variation of B. praecipua is reported and a DNA barcode (CO1) is provided for this species. The main differences between the three presently known species of Batella Holthuis, 1955 are discussed.